ISOLASI DAN UJI POTENSI Bacillus sp. ENTOMOPATOGEN LOKAL DARI TANAH ENDAPAN PENAMPUNGAN AIR TEMPAT PERINDUKAN NYAMUK Aedes aegypti - Meidita Ika Fauziyah Maswantari (PT Innovative Academic Journals, 2025)
Dengue Haemorrhagic Fever is an endemic disease caused by dengue virus and transmitted to humans through female Aedes aegypti mosquitoes. Surabaya, Sidoarjo and Gresik are 3 cities in East Java which have the highest density of Aedes aegypti larvae in 2013 – 2016. This research aims to isolate the Native Entomopathogenic Bacillus sp. from Soil Sediment of Water Reservoir of Breeding sites of Aedes aegypti and to know their potential biolarvacidal potency against Aedes aegypti larvae. The Soil sediments were taken from 10 sites in Surabaya, 10 sites in Sidoarjo and 10 sites in Gresik. Isolation of bacteria was performed using growth media of Bacillus sp., identified with Gram and spore stainings, and biolarvacidal potency test was performed on the third instar larval stage of Aedes Aegypti. Eight Native Entomopathogenic Bacillus sp. were isolated and those isolates were toxic to the third instar larvae of Aedes Aegypti more than 50% mortality. The highest level of killing power of these Bacillus sp. are isolate from Gresik, G6.4 which has 100% mortality, then followed by isolates from Surabaya, S7.3 and S4.3 which has 96,7% mortality and S4.5 which has 80% mortality at 48 hours exposure time with the same optical density (A600 nm = 0,8).